SPECIFIC FEATURES OF TEACHING SYNTAX IN PRIMARY GRADES (International journal of artificial intelligence, 2026)
This article is devoted to the problem of the formation of syntactic concepts of pupils in the lessons of the mother tongue of the primary class. In it, the difficulties in the formation of syntactic concepts of students in elementary class native language classes and the specific aspects of overcoming them are highlighted on the basis of experiments.